1978
DOI: 10.1159/000250904
|View full text |Cite
|
Sign up to set email alerts
|

Repigmentation of Hair Following Photosensitive Dermatitis

Abstract: A case of repigmentation of the scalp hair following photosensitive dermatitis is reported. The possible clinical application of this observation has been discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

1979
1979
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 4 publications
0
6
0
Order By: Relevance
“…Localized hypertrichosis may be observed in patients treated with oral photochcmotherapy (Singh & Lai, 1967;Braun-Falco, Hoffman & Plewig, 1976), and favourable results have been obtained in the treatment of alopecia areata treated with PUVA (Sidi & Bourgeois-Spinasse, 1955;Weissman etal.^ 1978). Repigmentation of white hair after light exposure also suggests direct stimulation of hair follicle melanocytcs (Bhutani et al, 1978). Improvement in vitiligo seems to occur clinically in successive waves.…”
Section: Discussionmentioning
confidence: 95%
“…Localized hypertrichosis may be observed in patients treated with oral photochcmotherapy (Singh & Lai, 1967;Braun-Falco, Hoffman & Plewig, 1976), and favourable results have been obtained in the treatment of alopecia areata treated with PUVA (Sidi & Bourgeois-Spinasse, 1955;Weissman etal.^ 1978). Repigmentation of white hair after light exposure also suggests direct stimulation of hair follicle melanocytcs (Bhutani et al, 1978). Improvement in vitiligo seems to occur clinically in successive waves.…”
Section: Discussionmentioning
confidence: 95%
“…[78][79][80] Hair darkening has also been described after X-ray irradiation and following electron beam therapy. [51] Shaffrali et al reported darkening of gray hair in two patients with porphyria cutanea tarda.…”
Section: Management Managementmentioning
confidence: 99%
“…Verbov 9 subsequently described a case of erosive candidiasis of the scalp in a 72‐year‐old woman, with regrowth of black hairs in the previously inflamed areas. Another patient with an exudative red dermatosis on sun‐exposed areas of the skin and scalp was noticed to have darkening of the roots of the hair at all previously inflamed sites, once the condition was treated 10 . Hair darkening has also been described after X‐irradiation of the scalp, 11 psoralen plus ultraviolet A therapy for Sézary syndrome, 12 and following electron beam therapy 13…”
Section: Discussionmentioning
confidence: 99%